ANALISIS KINERJA KEUANGAN PT WIJAYA KARYA TBK TAHUN 2007 - 2011 - ADIEL NURINDRA, DIMAS Adiel (Jurnal Akuntansi AKUNESA, 2013)
The construction development more or less always affect the development of economic inmany ways. Therefore, construction development is very important cause for economicdevelopment to develop in good ways. One of the company that run it bussines in buildingcontruction is PT Wijaya Karya Tbk. The purpose of this article to know the financialperformance of PT Wijaya Karya Tbk within year 2007 to year 2011. With descriptionresearch trough calculating and analyzing the financial report. The author reach aconclusion that the financial performance of PT Wijaya Karya Tbk are healthy.Keywords : develop, financial performance, calculating, analyzing, healthy.